2006
DOI: 10.3102/00028312043002219
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic Management on Student Achievement

Abstract: Proponents of school restructuring often promote the purported benefits of professional forms of management that call for staff cooperation and collegiality, teachers' participation in school decision making, and supportive leadership by school principals. A theoretical perspective on organizations known as contingency theory refers to such management patterns as "organic management." This study examined the relationships between organic management and growth in student achievement in elementary and secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 39 publications
6
37
0
Order By: Relevance
“…Furthermore, the analytical distinction between organic and mechanistic organizational arrangements may also be necessary (Rowan, 1990(Rowan, , 2002a(Rowan, , 2002b. Whereas mechanistic arrangements include centralized decision making, clearly defined positions, and hierarchical relations, organic arrangements involve staff in decision-making processes and cooperative relationships (Miller & Rowan, 2006). While it is tempting to view schools where leaders almost equal or even outnumber other staff as more organic and less mechanistic, our case schools suggest that this may not always be the case.…”
Section: Factoring In the Informal Organizationmentioning
confidence: 79%
“…Furthermore, the analytical distinction between organic and mechanistic organizational arrangements may also be necessary (Rowan, 1990(Rowan, , 2002a(Rowan, , 2002b. Whereas mechanistic arrangements include centralized decision making, clearly defined positions, and hierarchical relations, organic arrangements involve staff in decision-making processes and cooperative relationships (Miller & Rowan, 2006). While it is tempting to view schools where leaders almost equal or even outnumber other staff as more organic and less mechanistic, our case schools suggest that this may not always be the case.…”
Section: Factoring In the Informal Organizationmentioning
confidence: 79%
“…In contrast, controlling principals less often had and met state or district goals and were also male. Miller and Rowan (2006) argue that more organic forms of leadership, such as shared instructional leadership, do not always influence an increase in student achievement. Future research should test a mediated (Hallinger & Heck, 1996) model of leadership and school and teacher conditions to examine whether or not these types of principals influence student success.…”
Section: Discussionmentioning
confidence: 99%
“…(pp. 382-383) Our assertion of a context-based leadership extends beyond correctly supporting teachers and effective instruction through either controlled or shared leadership (see Firestone & Wilson, 1985;Miller & Rowan, 2006;Rowan, 1990). Each characteristic of the school, students, teachers, and principal influences a principal's leadership behavior in a different way (Glasman & Heck, 1992;Goldring et al, 2008;Hallinger & Murphy, 1986;Krüger, Witziers, & Sleegers, 2007;Mayrowetz, Murphy, Louis, & Smylie, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research into models that did not have formal structures has shown a lack of success (Gordon and Seashore, 2009;Miller and Rowan, 2006). The drawback to informal organic improvement efforts that seek to engage multiple stakeholders is that they must reinvent the wheel, rather than building on what others have learned through implementation and research.…”
Section: Organic Approaches To School Parent and Community Partnershipsmentioning
confidence: 99%